Phase II Pragmatic Randomized Controlled Trial of Patient-Led Therapies (Mirror Therapy and Lower-Limb Exercises) During Inpatient Stroke Rehabilitation. (October 2015) - Tyson, Sarah; Wilkinson, Jack; Thomas, Nessa; Selles, Ruud; McCabe, Candy; Tyrrell, Pippa; Vail, Andy
Background and objective. Patient-led therapy has the potential to increase the amount of therapy patients undertake during stroke rehabilitation and to enhance recovery. Our objective was to assess the feasibility and acceptability of 2 patient-led therapies during the acute stages of stroke care: mirror therapy for the upper limb and lower-limb exercises for the lower limb. Methods. This was a blind assessed, multicenter, pragmatic randomized controlled trial of patient-led upper-limb mirror therapy and patient-led lower leg exercises. Stroke survivors with upper and lower limb limitations, undergoing inpatient rehabilitation and able to consent were recruited at least 1 week poststroke. Results. Both interventions proved feasible, with >90% retention. No serious adverse events were reported. Both groups did less therapy than recommended; typically 5 to 15 minutes for 7 days or less. Participants receiving mirror therapy (n = 63) tended to do less practice than those doing lower-limb exercises (n = 31). Those with neglect did 69% less mirror therapy than those without ( P = .02), which was not observed in the exercise group. Observed between-group differences were modest but neglect, upper-limb strength, and dexterity showed some improvement in the mirror therapy group. No changes were seen in the lower-limb group. Conclusions. Both patient-led mirror therapy and lower-limb exercises during inpatient stroke care are safe, feasible, and acceptable and warrant further investigation. Practice for 5 to 15 minutes for 7 days is a realistic prescription unless strategies to enhance adherence are included.